Species Richness and Abundance of Reef-Building Corals in the Indo-West Pacific: The Local–Regional Relation Revisited - DeVantier, Lyndon; Turak, Emre; Szava-Kovats, Robert (Frontiers in Marine Science, 2020)
The degree to which biotic communities are regionally enriched or locally saturated, and roles of key structuring processes, remain enduring ecological questions. Prior studies of reef-building corals of the Indo-west Pacific (IWP) found consistent evidence of regional enrichment, a finding subsequently questioned on methodological grounds. Here we revisit this relation, and associated relations between richness and abundance (as ‘Effective Number of Species’), and coral cover, used as a proxy for disturbance and competition. From 1994 to 2017, we sampled > 2,900 sites on shallow (typically < 8-10m below reef crest) and deep reef slopes in 26 coral ecoregions, from Arabia to the Coral Triangle, Eastern Australia, Micronesia and Fiji, for a total pool of 672 species. Sampling intensity varied among ecoregions, but always approached asymptotic richness. Local coral communities on both shallow and deep reef slopes were, on average, comprised of 25 percent of regional pools, ranging from 12 to 43 percent for individual ecoregions. Richest individual shallow and deep sites, averaged across all ecoregions, comprised 42 and 40 percent of regional pools, ranging from 30 to 60 percent, highest in environmentally marginal ecoregions. Contrary to prior studies, analyses using log-ratio regression indicated that IWP coral communities were mostly intermediate between regionally enriched and locally saturated. Strongest evidence of regional enrichment occurred on shallow reef slopes, consistent with these being most susceptible to disturbance. Unimodal curvilinear relations between local richness and coral cover provide support for disturbance mediation and competitive exclusion. IWP coral communities are clearly dynamic, shaped by biological, ecological and oceanographic processes and disturbance regimes that influence reproduction, dispersal, recruitment and survival. Yet there is also evidence for a degree of local saturation and facilitation, consistent with a niche-neutral model of community assembly. The richest sites hosted > 200 species, > 40 percent of regional pools and > 25 percent of the IWP total. For deep and shallow sites combined, the highest local tally reached 280 species ha-1. These places may represent the asymptote of local richness in reef-building corals, rare examples of the ecological complexity for which these increasingly endangered communities are justly renowned.